Yes and No: A Critical Response to F. Gerald Downing. (September 2017) - Keith, Chris
This essay replies to F. Gerald Downing's critical response to my article 'The Narratives of the Gospels and the Historical Jesus: Current Debates, Prior Debates and the Goal of Historical Jesus Research' (Keith 2016). I focus on four matters: 'authenticity', 'memory theory', 'tradition' and the concept of going 'behind' the text.